Optimizing Tomato Water and Fertilizer Uses in Smallholder Farms in South Africa Using the Piloten Model. (2nd October 2016) - Albasha, R.; Jovanovic, N.; Cheviron, B.; De Clercq, W.; Mailhol, J.‐C.
Abstract: The objectives of this paper are twofold: (i) to calibrate and validate the PILOTEN crop model for tomato ( Solanum lycopersicum L.), and (ii) to use the model to examine the response of tomato yield to different irrigation and fertilization scheduling scenarios under varying climatic conditions in order to draw up management recommendations for smallholder farms. The calibration and validation were performed by using data collected from field experiments carried out in the north‐east of South Africa, on shallow Ferrosol and Luvisol soils. The scenarios dealt with: (i) the initial soil‐water availability (fulfilling or not the soil‐water reserve at planting); (ii) the irrigation dose frequency (high versus low irrigation doses ranging from 10 to 40 mm per application); (iii) the fertilization dose frequency (full versus split fertilization application). The results indicated that only the fertilization scheduling may significantly affect tomato yields, while irrigation scheduling has a minor role. However, compared to the local official irrigation guidelines, it is recommended to slightly increase the irrigation doses during the first 4 weeks of growth for tomato grown between early September and mid‐December, and to slightly decrease the doses in the second part of the growing cycles starting in February and May. It is also suggested to avoid applying the entire fertilizer dose after seedling planting for tomato grown between mid‐February and late June. Copyright © 2020 John Wiley & Sons, Ltd. Résumé: Ce travail a un double objectif: (i) calibrer et valider le modèle Piloten pour la tomate ( Solanum lycopersicum L.) et (ii) utiliser le modèle pour analyser la réponse du rendement de la tomate à différents scénarios d'irrigation et de fertilisation, sous différentes conditions climatiques, afin de proposer des recommandations de conduites culturales aux petites exploitations. Le calage et la validation du modèle ont été effectués en utilisant des données recueillies par des expérimentations menées dans le nord‐est de l'Afrique du Sud, sur des Ferrosols et des Luvisols peu profonds. Les scénarios ont traité: (i) de la disponibilité initiale en eau du sol (réserve en eau du sol reconstituée ou non à la plantation); (ii) du couple dose‐fréquence d'irrigation (doses d'irrigation élevées à faibles allant de 10 à 40 mm par application); (iii) du couple dose‐fréquence de fertilisation. Les résultats ont indiqué que seul le calendrier de la fertilisation peut affecter de manière significative les rendements de la tomate, tandis que le calendrier d'irrigation joue un rôle mineur. En comparaison avec les recommandations locales de la gestion de l'irrigation et de la fertilisation de la tomate, il est recommandé d'augmenter légèrement les doses d'irrigation pendant les 4 premières semaines de croissance pour la tomate cultivée entre le début septembre et la mi‐décembre, et de diminuer légèrement les doses dans la deuxième partie du cycle de croissance commençant en février et en mai. Il est également suggéré d'éviter l'application de la totalité de la dose d'engrais après les semis de tomate cultivée entre mi‐février et fin‐juin. Copyright © 2020 John Wiley & Sons, Ltd.